Method and Characteristics of Gender Education Research in the Digital Age: Literature Review and Research Outlook - Siying Pu (Journal of Advanced Research in Education, 2024)
Since the 18th National Congress of the Communist Party of China, the research on gender education has shown a positive trend. With the help of CNKI, this paper searched the main literature related to “gender education in the digital age” in recent years and has found that the academic circle had done a lot of research on the specific context of gender education, the concept analysis of gender education and the method of gender education, and has broadened the research horizon and practice path of gender education. However, there are methods in the research that ignore the methodology of system construction, or emphasize quantitative analysis over qualitative, which needs to focus more on the core concept of gender education, to construct gender education methodology system with Chinese characteristics, and to enhance the practical application of gender education in the process of social transformation and upgrading, in order to better achieve the free and comprehensive development of every individual.